2003
DOI: 10.1097/01.aud.0000069228.46916.92
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Labeling on Outcome Measures

Abstract: The results of this investigation indicate a need for double-blinding in hearing aid research aimed at assessing the effectiveness of newer technologies, as well as a need for clinicians to critically evaluate the research describing the potential advantages of certain circuit options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 11 publications
4
49
2
Order By: Relevance
“…There are studies in which little or no relation between reported benefit and measured benefit is found (e.g., Cox & Alexander, 1992;Haggard, Foster, & Iredale, 1981). Yet other investigations find participants reporting strong preferences for one of two pairs of hearing aids worn during a study, even though both pairs of hearing aids were identical (Bentler, Niebuhr, Johnson, & Flamme, 2000;McClymont, Browning, & Gatehouse, 1991). Finally, there are investigations in which hearing aid setting preferences in the laboratory do not transfer to real-world use (Preminger & Cunningham, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…There are studies in which little or no relation between reported benefit and measured benefit is found (e.g., Cox & Alexander, 1992;Haggard, Foster, & Iredale, 1981). Yet other investigations find participants reporting strong preferences for one of two pairs of hearing aids worn during a study, even though both pairs of hearing aids were identical (Bentler, Niebuhr, Johnson, & Flamme, 2000;McClymont, Browning, & Gatehouse, 1991). Finally, there are investigations in which hearing aid setting preferences in the laboratory do not transfer to real-world use (Preminger & Cunningham, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…There are others in which little or no relationship between reported benefit and measured benefit is found (Cox & Alexander, 1992;Haggard, Foster & Iredale, 1981). Yet other investigations find subjects reporting strong preferences for one of two pairs of hearing aids worn during studies in which both pairs of hearing aids were identical (Bentler, Niebuhr, Johnson & Flamme, 2000;McClymont, Browning & Gatehouse, 1991). It is difficult to reconcile conflicting data such as these, in part because the materials and formats used for measuring speech performance are so very different from the questionnaires used for subjective evaluations.…”
mentioning
confidence: 89%
“…Relatively few improvements were obtained with objective measurements. It was also demonstrated by Bentler et al 120 in a clever experiment that there was a significant halo effect in that if a subject believed a hearing aid to be a digital instrument, then the subjective assessment of the hearing aid was likely to be more positive than if the subject believed otherwise.…”
Section: Comparing Analog and Digital Instrumentsmentioning
confidence: 92%